2018
DOI: 10.1371/journal.pone.0199984
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the enigmatic crocodyliform "Goniopholis" paulistanus Roxo, 1936: Historical approach, systematic, and description by new materials

Abstract: The Crocodyliformes are the most represented vertebrate clade in the Upper Cretaceous sequences of the Bauru Group, Paraná Basin. However, some of the species described have an uncertain taxonomic status and phylogenetic position. For instance, “Goniopholis” paulistanus has been assigned as a nomem dubium, due to its description being based on scarce material. The “G”. paulistanus specimens (i.e. teeth and a left tibia) were discovered in two different localities in São Paulo state: Mirandópolis and Valparaíso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 122 publications
(215 reference statements)
0
6
0
Order By: Relevance
“…Particularly, Baurusuchus occurs in the state of São Paulo with Caipirasuchus stenognathus and other sphagesaurid material (e.g., Armadillosuchus arrudai ), contrary to what is seen in Triângulo Mineiro. Recently, Pinheiro et al (2018) identified four Crocodyliformes Assemblages Zones (AZ) within levels of the Adamantina and correlated or partially correlated formations in Minas Gerais and São Paulo states within a sequence stratigraphic framework. The authors also mentioned the lack of appropriated biostratigraphic correlations and the difficult to perform it, in part due to taxonomic problem with some taxa and also biases in the fossil record.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, Baurusuchus occurs in the state of São Paulo with Caipirasuchus stenognathus and other sphagesaurid material (e.g., Armadillosuchus arrudai ), contrary to what is seen in Triângulo Mineiro. Recently, Pinheiro et al (2018) identified four Crocodyliformes Assemblages Zones (AZ) within levels of the Adamantina and correlated or partially correlated formations in Minas Gerais and São Paulo states within a sequence stratigraphic framework. The authors also mentioned the lack of appropriated biostratigraphic correlations and the difficult to perform it, in part due to taxonomic problem with some taxa and also biases in the fossil record.…”
Section: Discussionmentioning
confidence: 99%
“…The Vale do Rio do Peixe, Presidente Prudente, São Jose do Rio Preto, and Araçatuba formations were the units proposed in substitution to part of the Adamantina Formation ( Fernandes, 1998 ; Fernandes & Coimbra, 2000 ). Nevertheless, the use of the Adamantina Formation is still favoured over the alternative terminology (applied to the state of São Paulo state), especially in works regarding the outcrops in the Triângulo Mineiro region, in which Campina Verde is located ( Paula e Silva, Kiang & Caetano-Chang, 2009 ; Batezelli, 2010 ; Batezelli & Ladeira, 2016 ; Menegazzo, Catuneanu & Chang, 2016 ; Pinheiro et al, 2018 ). Thus, we opted to follow these more recent geological contributions and favor use of Adamantina Formation in the Triângulo Mineiro region.…”
Section: Introductionmentioning
confidence: 99%
“…This unit was developed during the Late Cretaceous, deposited during the Gondwana breaking-up (Fernandes & Coimbra, 2000). The Bauru Group crops out in parts of various Brazilian states, and a detailed stratigraphic review can be seen in some more recent works (e.g., Pinheiro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among the eight formations that compose the Bauru Group (sensu Pinheiro et al, 2018), in the Gurinhatã municipality outcrops the Adamantina and Marília formations (Fig. 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation